2019
DOI: 10.1111/jcmm.14385
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐629 regulates hypoxic pulmonary vascular remodelling by targeting FOXO3 and PERP

Abstract: Pulmonary arterial hypertension (PAH) is featured by the increase in pulmonary vascular resistance and pulmonary arterial pressure. Despite that abnormal proliferation and phenotypic changes in human pulmonary artery smooth muscle cells (HPASMCs) contributing to the pathophysiology of PAH, the underlying molecular mechanisms remain unclear. In the present study, we detected the expression of miR‐629 in hypoxia‐treated HPASMCs and explored the mechanistic role of miR‐629 in regulating HPASMC proliferation, migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…MicroRNAs (miRNAs), small non‐coding RNAs 21–23 nucleotides in length, have been reported to participate in many biological processes (e.g., cell proliferation, migration, invasion and apoptosis) [ 122 ]. For instance, microRNA-629 promotes PASMC proliferation and migration, suppresses apoptosis by downregulating the target of forkhead box O3 (FOXO3) and p53 apoptosis effector related to PMP‐22 (PERP) in hypoxia-induced PASMCs [ 123 ]. Another report also showed that overexpression of microRNA-150 relieved pulmonary fibrosis and collagen I in hypoxia-induced rats, and the specific mechanism is thought to occur through inhibition of the AKT/mTOR signalling pathway [ 124 ].…”
Section: Therapy For Pahmentioning
confidence: 99%
“…MicroRNAs (miRNAs), small non‐coding RNAs 21–23 nucleotides in length, have been reported to participate in many biological processes (e.g., cell proliferation, migration, invasion and apoptosis) [ 122 ]. For instance, microRNA-629 promotes PASMC proliferation and migration, suppresses apoptosis by downregulating the target of forkhead box O3 (FOXO3) and p53 apoptosis effector related to PMP‐22 (PERP) in hypoxia-induced PASMCs [ 123 ]. Another report also showed that overexpression of microRNA-150 relieved pulmonary fibrosis and collagen I in hypoxia-induced rats, and the specific mechanism is thought to occur through inhibition of the AKT/mTOR signalling pathway [ 124 ].…”
Section: Therapy For Pahmentioning
confidence: 99%
“…3C), likely to indicate a direct transcriptional regulatory effect. Increase in the expression of PTPMT1 and reduction in the expression of other gene regulators of vascular remodelling identified by RNAseq, SERPINE1 (Simone, Higgins et al, 2014), PERP (Zhao, Chen et al, 2019), DUSP5 (Chen, Zmuda et al, 2020), NOTCH3 (Li, Zhang et al, 2009) and c-myb (You, Mungrue et al, 2003) were validated by qPCR ( Fig. 3D and Appendix Figure S2).…”
Section: Identification Of Mir-150-regulated Genesmentioning
confidence: 81%
“…FOXO3, as a transcriptional factor and important mediator, has been shown to contribute to the protective effects of cardiovascular fibrosis and ischemia-reperfusion (I/R) injury (34). miR-629 promoted cell proliferation, migration and apoptosis by targeting FOXO3 in vascular remodeling (35). The functions of miR-124 on hypertensive pulmonary fibroblast proliferation were mediated through FOXO3/cdk inhibitor cdkn1a signaling (36).…”
Section: Discussionmentioning
confidence: 99%